The Holy Qur'an's Borrowed Words in Malay and its Role in Teaching Arabic to Malay in South - East Asia - Baioumy, Nashaat Abdelaziz Abdelqader (International Journal of Psychosocial Rehabilitation, 2020)
The words of the Holy Qur'anare commonly spoken in the languages of non-Arabic-speaking Muslims, such as Malay, Urdu, Turkish, Kazaks and others. And the relationship is close and long between the Holy Qur'an and the teaching and learning of Arabic. Some studies Has built curriculum to teach the Arabic to speakers of other languages in the light of the text of the Holy Qur'an; but still few, as they did not pay attention to take advantage of the language of the Holy Qur'an, which borrowed in these languages to help learners, speakers of non-Arabic in learning Arabic. Therefore, the goal of current research is to analyze and describe some of the lexical and semantic characteristics of words of the Holy Qur'an borrowed in the Malay language, and then put the proposed concept to take advantage of them in teaching Arabic to speakers of other languages in Malay. To achieve this objective, the research relied on two approaches: introspective and analytical descriptive. The research concluded a number of findings, including: that the language of the Holy Qur'an, which borrowed in Malay are common in all areas and semantic vessels, particularly in the religious sphere. Those words represented an important entry point for teaching and for building a curriculum for teaching Arabic in Malay. As recommended by the research, preparing books for teaching Arabic in countries of South-East Asia in the light of these words, holding courses for teachers to train them to take this advantage, and start further linguistic studies of grammar and rhetoric related to that.